2016
DOI: 10.15537/smj.2016.10.14967
|View full text |Cite
|
Sign up to set email alerts
|

A novel missense mutation in the C2C domain of otoferlin causes profound hearing impairment in an Omani family with auditory neuropathy

Abstract: Objectives:To identify genetic defects in an Omani family diagnosed with deafness.Methods:A cross-sectional association study was conducted at the Department of Biochemistry, College of Medicine and Health Sciences, Sultan Qaboos University, Al-Khoud, Oman and the Centre of Medical Genetics, University of Antwerp, Antwerp, Belgium between August 2010 and September 2014. Microsatellites markers for nine non-syndromic genes were used to genotype the defective locus using the extracted DNA from family members. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Among them, the G>A nucleotide change at position 4960 was located in the exon/intron junction that was expected to result in aberrant splicing, thus causing an abnormal amino acid chain of the otoferlin protein. The reported missense mutation c.1469C>G was located in the relevant C2C domain and was confirmed to affect the function of protein products [23]. The mutation c.2675A>G was found in the region between the C2C and C2D domains and was predicted to result in deleterious splicing.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Among them, the G>A nucleotide change at position 4960 was located in the exon/intron junction that was expected to result in aberrant splicing, thus causing an abnormal amino acid chain of the otoferlin protein. The reported missense mutation c.1469C>G was located in the relevant C2C domain and was confirmed to affect the function of protein products [23]. The mutation c.2675A>G was found in the region between the C2C and C2D domains and was predicted to result in deleterious splicing.…”
Section: Discussionmentioning
confidence: 87%
“…Pathogenic variants in the OTOF gene identified in this study. 1469C>G) in the OTOF gene[23,24,26]. Combining the verification by the Sanger sequencing in the corresponding parents and siblings (Table3), variants c.[2688del];[2688del], c.[4960G>A];[1469C>G], and c.[2675A>G];[2977_ 2978del] were confirmed to be likely pathogenic/pathogenic for three families.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Genetic mutation in otoferlin leads to severe hearing impairment resulting from improper HC synaptic development and lack of synaptic vesicle exocytosis. [ 95 96 ]…”
Section: O Toferlinmentioning
confidence: 99%
“…A survey conducted in 2016 indicated that up to 49% of Omani marriages were consanguineous [1]. As a result, 70% of hearing loss cases in Oman were reported as possible inherited forms and until now, two genes have been reported to be involved in nonsyndromic autosomal recessive genetic deafness in Oman, MYO15A, and Otoferlin [2][3][4].…”
Section: Introductionmentioning
confidence: 99%